Smart Sensing Technologies for Agriculture - Adamchuk, Viacheslav; Sudduth, Kenneth; Biswas, Asim (MDPI - Multidisciplinary Digital Publishing Institute, 2020)
"Smart Sensing Technologies for Agriculture" is a Special Issue of Sensors that includes 14 research papers on diverse topics about the measurement of physical, chemical, and biological characteristics of soil, plants, and animals related to modern farming practices.